Contrasting Mathematical Phenomena and Concepts in Ethnomathematics through Etic and Emic Approaches: A Study of Dhikr Jahar Practices in Tariqa Qodiriyah Naqsyabandiyah Ma’had Suryalaya - Yulianto, Eko; Wahyudin, Wahyudin; Tafsir, Ahmad; Prabawanto, Sufyani (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
Ethno-mathematical research trends pioneered by D'Ambrosio are on the rise, especially in Indonesia as a nation with high cultural diversity which has a lot of potential researches to be explored. This paper has two major objectives, first to explore the importance of the role of mathematics in the practice of Dhikr Jahar in Tariqa Qodiriyyah Naqsyabandiyyah and second to contrast the differences between mathematical phenomena and mathematical concepts in ethnomathematics research. Attempts to contrast the mathematical phenomena and mathematical concepts in ethnomathematics was expected to provide a sharper highlight in the writing of ethnomathematics research. This research used qualitative methods with two approaches, namely ethnography and phenomenology. The locations of the research are at Pondok Pesantren Suryalaya-Sirnarasa and Padepokan Talangraga Tasikmalaya with observations for 9 months in the first stage and then 6 months in the second stage. The number of respondents interviewed in this research were 48 people. Data processing was performed using the Nvivo 12 Plus. The results showed that there are many mathematical phenomena in the practice of Dhikr Jahar Ikhwan TQN. In carrying out the practice of dhikr, the Ikhwan used a mathematical concept with two events, fingers and prayer beads aids. The concept of counting in dhikr was used strictly by the Ikhwan. They believe that numbers have an important role in the quantity of dhikr. Contrasting mathematical phenomena and mathematical concepts can be done with an emic and etic approach and is expected to become an alternative style in ethnomathematics research.